Learning Objects for use in Interactive Digital Television - Zancanaro, Airton; Pinto, Claudia Alexandra de Souza; Todesco, José Leomar; Santos, Neri dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
Digital Television in Brazil is being implemented with extensive support of public policies to promote social inclusion through e-government services and the formation of a network of distance education. The Interactive TV (iDTV) allows a lot of services that combine video and data offering the user more control over the content and services compared to traditional services of TV, thus becoming an interactive form of communication. Consequently, new content should be researched and developed in the form of learning objects (LO) specifically for T-learning. This article aims to discuss papers existing in international databases whose subject is about adaptation of LO to the context of iDTV. The results of the research have presented that there are several initiatives for the production of LO for iDTV in the world, with emphasis on the T-MAESTRO project and the ATLAS project in Spain and the BEACON project in Brazil/Europe. However, it is perceived that the development of the content and services are in the beginning, because today is largely used primarily for the information and communication technologies and should be adapted to iDTV.